2016
DOI: 10.1016/j.devcel.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Visceral Embryonic Midline Is a Dynamic Process that Requires Bilaterally Symmetric BMP Signaling

Abstract: The vertebrate body plan contains both dorsal and ventral midline structures. While dorsal midline structures have been extensively studied, formation of ventral midline structures, and how they become aligned with the dorsal midline, is a fundamental aspect of vertebrate development that is poorly understood. This study uses the chick dorsal mesentery (DM) as a model for investigating the formation of ventral midline structures. We document formation of the DM by epithelial-to-mesenchymal transition (EMT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
1
34
1
Order By: Relevance
“…The stages prior to the appearance of aortic hematopoietic clusters are characterized by widespread morphological changes in the AGM region. Our previous studies and those of others have shown that the coelomic epithelium (CE) undergoes Epithelial to Mesenchymal Transition (EMT) to give rise to the sub aortic mesenchyme and dorsal mesentery, and that this subaortic mesenchyme plays an essential role in Runx1 endothelial cell expression and the formation of hematopoietic cells (Arraf et al, 2016;Richard et al, 2013). However, it is not known whether this mesenchyme plays a role in early aortic HE specification.…”
Section: Introductionmentioning
confidence: 99%
“…The stages prior to the appearance of aortic hematopoietic clusters are characterized by widespread morphological changes in the AGM region. Our previous studies and those of others have shown that the coelomic epithelium (CE) undergoes Epithelial to Mesenchymal Transition (EMT) to give rise to the sub aortic mesenchyme and dorsal mesentery, and that this subaortic mesenchyme plays an essential role in Runx1 endothelial cell expression and the formation of hematopoietic cells (Arraf et al, 2016;Richard et al, 2013). However, it is not known whether this mesenchyme plays a role in early aortic HE specification.…”
Section: Introductionmentioning
confidence: 99%
“…Although, in both, looping results from differential growth between the gut tube and mesentery, the degree of differential growth is twofold higher in the chick than the finch (1). Because bone morphogenetic proteins (BMPs) have been strongly implicated in other aspects of gut and mesentery organogenesis (13)(14)(15)(16)(17)(18), we compared BMP signaling in the embryonic chick and finch dorsal mesentery by immunofluorescent detection of phosphorylated Smad 1/5/8. In the chick, phosphoSmad levels temporally correlated with the progression of looping morphogenesis ( Fig.…”
Section: Bmp Signaling Is Enriched In the Looping Chick Dorsal Mesentmentioning
confidence: 99%
“…The potential of the UCS to act as a switch that may activate or repress depending on cell type is highly relevant in the context of embryogenesis where Bmp2 expression is highly dynamic. A recent study supports the idea that midline positioning of the dorsal mesentery depends on the relative, rather than the actual, amount of BMP signaling on the left and right sides of the developing embryo (Arraf, Yelin, Reshef, Kispert, & Schultheiss, 2016;Gavrilov and Lacy, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…The potential of the UCS to act as a switch that may activate or repress depending on cell type is highly relevant in the context of embryogenesis where Bmp2 expression is highly dynamic. A recent study supports the idea that midline positioning of the dorsal mesentery depends on the relative, rather than the actual, amount of BMP signaling on the left and right sides of the developing embryo (Arraf, Yelin, Reshef, Kispert, & Schultheiss, ; Gavrilov and Lacy, ). By potentially up‐regulating BMP2 synthesis in some tissues, but down‐regulating in other tissues, the UCS deletion would disrupt the relative levels of BMP2 in developing tissues and profoundly influence tissue morphogenesis.…”
Section: Discussionmentioning
confidence: 63%